Molecular characterisation and expression profiles of phosphate-deficiency inducible phosphate transporter 1 and phosphate starvation response gene families in Elaeis guineensis Jacq. - Hamzah, Muhammad Luqman (2020)
Phosphate transporter 1 (PHT1) proteins are responsible for acquisition of phosphate (Pi) by the plants. The transcription factor involved in the transcriptional regulation of PHT1 is phosphate starvation response (PHR). Pi uptake by PHT1 needs to across a steep concentration gradient from lower Pi concentration in soil, usually less than 10 µM into high Pi concentration inside the plant cells which are in the range of 5 to 20 mM. Moreover, the oil palm plantation requires high fertilizer input to maintain high productivity. But high fertilizer input may cause water pollution. Besides that, Pi rock, the major source of Pi fertilizer is envisaged to be exhausted in next 40 to 70 years. This will cause catastrophic effect to agriculture industry. The objectives of this study were to perform genome-wide molecular characterization of PHT1 and PHR genes in oil palm and study their expression profiles under different Pi-deficient conditions as well as to determine the specific location of EgPHR2 protein using the subcellular localization technique. Using the PHT1 and PHR coding sequences of Arabidopsis thaliana and Oryza sativa as the query sequences for BLAST search to find the homologues of PHT1 and PHR genes in oil palm resulted in the identifications of 10 EgPHT1 and three EgPHR genes. All EgPHT1 proteins contain GGDYPLSATIxSE, the signature sequence of PHT1. All EgPHR have MYB binding domain and coiled–coil domain characteristic of PHR at their C-terminal regions and one unique SOG2 domain for EgPHR1. Analysis of 1500 bp of promoter sequences on four selected EgPHT1 genes using PlantCare and New PLACE databases showed that two of the EgPHT1 (EgPHT1;4 and EgPHT1;7) contain the PHR binding site (P1BS) motif. In addition, other Pi deficiency responsive motifs including W-box and many E-box motifs were found on EgPHT1;4, EgPHT1;6 and EgPHT1;7 promoter sequences. The root specific motif, ROOTMOTIFTAPOX1 was also discovered on EgPHT1;4, EgPHT1;6 and EgPHT1;7. The oil palm seedlings were grown hydroponically under Pi sufficient (+P; 1.93 mM), low Pi (LP; 0.1 mM) and Pi deficient (-P) conditions. The expression of four of the EgPHT1 and two of the EgPHR was studied by real-time quantitative PCR (qPCR) in the roots and leaves of these seedlings. All genes showed enhanced expression in roots at -P compared to +P. The expression profile of EgPHR2 which showed upregulation at LP compared to +P and further increase at -P correlated with EgPHT1;4 and EgPHT1;7 that possess P1BS motif in their promoter sequences. EgPHR2, as a potential early transcriptional regulator for Pi starvation was detected to be nuclear localized through subcellular localization experiment, a key characteristic of a transcription factor. This study suggests all four analyzed EgPHT1 and two EgPHR play critical role in responding to Pi deprivation in oil palm. EgPHT1;4 and EgPHT1;7 which possess the P1BS motif are potentially upregulated by EgPHR2 as an early response mechanism against Pi starvation. The result from this study will help to fully map the Pi regulatory mechanism to enhance the Pi acquisition efficiency by oil palm.